How “Subclinical” is Subclinical Tuberculosis? An Analysis of National Prevalence Survey Data from Zambia - Stuck, Logan; van Haaster, Aimee Claire; Kapata-Chanda, Pascalina; Klinkenberg, Eveline; Kapata, Nathan; Cobelens, Frank (Clinical infectious diseases, 2022)
Pulmonary tuberculosis infection can manifest in different states, including subclinical tuberculosis. It is commonly defined as confirmed tuberculosis without the classic symptoms (commonly, persistent cough for ≥2 weeks). This narrow definition likely poses limitations for surveillance and control measures. The aims of the current study were to characterize the clinical presentation of tuberculosis; estimate the prevalence of subclinical tuberculosis among individuals with bacteriologically confirmed tuberculosis, using various definitions; and investigate risk factors for subclinical as opposed to clinical tuberculosis in a population-based survey. We conducted a secondary analysis of data from a nationally representative tuberculosis prevalence survey from Zambia in 2013-2014, in which participants were screened for tuberculosis based on chest radiographic findings and symptoms. Tuberculosis was defined as culture-positive or GeneXpert MTB/RIF test-positive sputum. Risk factors for subclinical tuberculosis were assessed by means of multivariable logistic regression. Of 257 participants with confirmed tuberculosis, 104 (40.5%) were without cough persisting ≥2 weeks. Only 23 (22.1%) of these did not present with any other common symptoms. Those without cough persisting ≥2 weeks frequently reported other symptoms, particularly chest pain (46.2%) and weight loss (38.5%); 36 (34.6%) reported experiencing other symptoms persisting ≥4 weeks. Female subjects were more likely to report no cough persisting ≥2 weeks, as were relatively wealthier individuals. The commonly used definition of subclinical tuberculosis includes a large proportion of individuals who have other tuberculosis-suggestive symptoms. Requiring cough ≥2 weeks for tuberculosis diagnosis likely misses many active tuberculosis infections and allows a large reservoir of likely transmissible tuberculosis to remain undetected.